The cost-effectiveness of different approaches to exercise and corticosteroid injection for subacromial pain (impingement) syndrome. (7th January 2021) - Oppong, Raymond; Jowett, Sue; Lewis, Martyn; Roddy, Edward; Ogollah, Reuben O; Zwierska, Irena; Datta, Praveen; Hall, Alison; Hay, Elaine; Shufflebotham, Julie; Stevenson, Kay; van der Windt, Danielle A; et al.
Abstract: Objectives: To determine whether physiotherapist-led exercise intervention and US-guided subacromial CS injection is cost-effective when compared with standard advice and exercise leaflet and unguided injection in patients with subacromial pain (impingement) syndrome. Methods: An incremental cost–utility analysis using patient responses to the five-level EuroQoL-5D (EQ-5D-5L) questionnaire was undertaken from a healthcare perspective alongside a 2 × 2 factorial randomized trial with 256 participants over a 12-month follow-up period. Uncertainty was explored through the use of cost-effectiveness acceptability curves. Results: The cost–utility analysis indicated that physiotherapist-led exercise was associated with an incremental cost of £155.99 (95% CI 69.02, 241.93) and 0.031 (95% CI −0.01, 0.07) additional quality-adjusted life-years (QALYs), an incremental cost-effectiveness ratio (ICER) of £5031 per QALY gained and an 85% chance of being cost-effective at a threshold of £20 000 per QALY gained compared with the advice and exercise leaflet. US-guided injection was associated with an incremental cost of £15.89 (95% CI −59.36, 109.86) and 0.024 (95% CI −0.02, 0.07) additional QALYs, an ICER of £662 per QALY gained and a 83% chance of being cost-effective at a threshold of £20 000 per QALY gained compared with unguided injection. Conclusion: Physiotherapist-led exercise was cost-effective compared with the advice and exercise leaflet, and US-guided injection was cost-effective when compared with unguided injection. Clinical trial registration: ISRCTN, http://www.isrctn.com, ISRCTN42399123